Reduction of Atherosclerosis in Cholesterol-Fed Rabbits and Decrease of Expressions of Intracellular Adhesion Molecule-1 and Vascular Endothelial Growth Factor in Foam Cells by a Water-Soluble Fraction of Polygonum multiflorum - Peng-Yuan Yang; Mohamad Radwan Almofti; Ling Lu; Hui Kang; Jing Zhang; Tie-Jun Li; Yao-Cheng Rui; Lian-Na Sun; Wan-Sheng Chen (Elsevier, 2005)
Polygonum multiflorum stilbeneglycoside (PMS) is a water-soluble fraction of Polygonum multiflorum Thunb., one of the most famous tonic traditional Chinese medicines, that has protective effects on the cardiovascular system. The purpose of the present study is to elucidate the effects of PMS on macrophage-derived foam cell functions and the reduction of severity of atherosclerosis in hypercholesterolemic New Zealand White (NZW) rabbits. NZW rabbits were fed for 12 weeks with a normal diet, a high cholesterol diet, or a high cholesterol diet associated with irrigation with different doses of PMS (25, 50, or 100 mg/kg). Treatment of NZW rabbits fed with high cholesterol diet with 100 mg/kg PMS attenuated the increase in plasma cholesterol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol, and plasma triglyceride. Treatment with 50 and 100 mg/kg PMS caused 43% and 60% decrease in atherosclerotic lesioned area ratio to total surface area, respectively. In U937 foam cells, PMS could decrease the high expression of intercellular adhesion molecule (ICAM)-1 protein and the vascular endothelial growth factor (VEGF) protein levels in the medium induced by oxidized lipoprotein when analyzed by flow cytometry. The results proved that PMS is a powerful agent against atherosclerosis and that PMS action could possibly be through the inhibition of the expression of ICAM-1 and VEGF in foam cells. Keywords:: atherosclerosis, Polygonum multiflorum, growth factor, cell adhesion molecule, macrophage